Arrhythmogenic Right Ventricular Dysplasia Diagnosed in a Patient with Long-term Undiagnosed Syncope - Avi Shah; Ramesh Patel; Sandeep Aggarwal (Journal of Clinical and Diagnostic Research, 2022)
Arrhythmogenic Right Ventricular Dysplasia (ARVD) is an inherited cardiomyopathy which represents progressive replacement of right ventricular myocardium with fibrofatty tissue. In the present case, a 42-year-old male presented to the hospital as he fell down, due to syncope. He had a history of recurrent syncopal in past 4-5 years. His chest radiogram revealed cardiomegaly (CT ratio 0.64), repeat electrocardiogram showed symmetric T-wave inversions and epsilon waves in right precordial V1, V2 and V3 leads, and echocardiogram revealed mild left ventricular dysfunction (ejection fraction - 45%) and dilated right atrium and ventricle. Cardiac Magnetic Resonance Imaging (MRI) confirmed the diagnosis of ARVD.The patient was advised for the placement of an Automatic Implantable Cardioverter Defibrillator (AICD), but he denied for this treatment. Thus, he was managed with anti-arrhythmic drugs and was advised for regular follow-up. The patient was followed-up for six months where episodes of syncope had significantly reduced to one in six months but need of AICD implantation was still there to avoid sudden cardiac death.